Describing the Evidence Base for Accreditation in Undergraduate Medical Education Internationally: A Scoping Review. (December 2019) - Tackett, Sean; Zhang, Christiana; Nassery, Najlla; Caufield-Noll, Christine; van Zanten, Marta
Abstract : Purpose: To summarize the state of evidence related to undergraduate medical education (UME) accreditation internationally, describe from whom and where the evidence has come, and identify opportunities for further investigation. Method: The authors searched Embase, ERIC, PubMed, and Scopus from inception through January 31, 2018, without language restrictions, to identify peer-reviewed articles on UME accreditation. Articles were classified as scholarship if all Glassick's criteria were met and as nonscholarship if not all were met. Author, accrediting agency, and study characteristics were analyzed. Results: Database searching identified 1, 379 nonduplicate citations, resulting in 203 unique, accessible articles for full-text review. Of these and with articles from hand searching added, 36 articles were classified as scholarship (30 as research) and 85 as nonscholarship. Of the 36 scholarship and 85 nonscholarship articles, respectively, 21 (58%) and 44 (52%) had an author from the United States or Canada, 8 (22%) and 11 (13%) had an author from a low- or middle-income country, and 16 (44%) and 43 (51%) had an author affiliated with a regulatory authority. Agencies from high-income countries were featured most often (scholarship: 28/60 [47%]; nonscholarship: 70/101 [69%]). Six (17%) scholarship articles reported receiving funding. All 30 research studies were cross-sectional or retrospective, 12 (40%) reported only analysis of accreditation documents, and 5 (17%) attempted to link accreditation with educational outcomes. Conclusions: Limited evidence exists to support current UME accreditation practices or guide accreditation system creation or enhancement. More research is required to optimize UME accreditation systems' value for students, programs, and society. Abstract : Supplemental Digital Content is available in the text.